Pengembangan Infrastruktur Jaringan Komputer PNP PSDKU Solok Selatan Menggunakan Metode Network Development Life Cycle (NDLC) - rosman, edwar; Flomina, Katrina; Hasanah, Miftahul; Febriani, Widya; Gaputra, Ideva (SOTVI - Society of Visual Informatics, 2024)
This research aims to analyze and design the computer network infrastructure at the Politeknik Negeri Padang (PNP) Program Studi Di luar Kampus Utama (PSDKU) South Solok in order to improve network performance. Currently there are 4 Optical Network Terminal (ONT) units from ISP Indihome with bandwidth for 2 ONTs of 100 Mbps and 1 ONT of 300 Mbps and 1 ONT specifically as a Wifi ID access point to meet the internet needs of lecturers, students and educational staff. However, there are problems identified, namely bandwidth management is not optimal, which results in a bottleneck on one of the ISP lines and not optimal use of the available bandwidth capacity and there is no back up if one of the ONTs has a problem. This research uses the Network Development Life Cycle (NDLC) method which consists of analysis, design, simulation, implementation, monitoring and management stages. In the initial stage, network requirements analysis and network topology design with the addition of a router are carried out. Network testing is carried out at the final stage to ensure that the new network infrastructure is able to work properly. The results of this research provide better internet network optimization in PNP PSDKU South Solok